PARAMETERS FOR THE STANDARDIZATION OF CHLOROPHYLL AND ASSESSMENT OF PS II QUANTUM EFFICIENCY FOR AVOCADO (Persea americana Mill) - Gutierrez Rodriguez, Edwin Antonio; Penariol, Mauricio Panizzi; Alves da Costa Aguiar, Pedro Luis [UNESP]; Panizzi, Rita de Cassia [UNESP]; Andrade, Renata Aparecida de [UNESP] (Univ Federal Uberlandia, 2017)
The standard physiological parameters for assessing stress physiology, of plants, such as chlorophyll index and photosystem II fluorescence, are essential for measuring reactions of plants to stress conditions. To help standardize the parameters for chlorophyll indices of chlorophylls a, b, and total and the fluorescence of photosystem II (Fv/Fm), which are physiological indicators of stress conditions, 6-mo-old seedlings of Persea americana Mill. cv. 'Duke7' and 'Toro canyon', were evaluated under shade house conditions. For each plant, chlorophyll indices were measured from the second through the fourteenth fully expanded leaves. Fluorescence was measured in the third, fifth, seventh, and ninth fully expanded leaf, and determined in function of both, time and intensity of the exposure light source, and the time for dark pre-acclimation of the leaf; was also compared right and left sides of the leaves. Chlorophyll indices were not different between the left and right sides of the leaves, but were different between varieties with 'Duke 7' having the highest value from the eighth leaf, while leaves tested for 'Toro canyon' did not show a difference. For Fv/Fm, there was an interaction among the three factors in both cultivars. A prolonged exposure time (nine seconds), short time for acclimation to darkness, and low intensity of exposure did not induce maximum fluorescence levels. On both avocado cultivars, exposure to maximum light intensity for 7 seconds after 25 to 30 minutes of acclimation to darkness, was the most favorable combination allowing the measurement of photosynthetic efficiency.
Keywords: Avocado; Chlorophyll index; Fv/Fm; Photosystem II; Physiological parameters